Development of educational graphical interfaces for radiation and propagation of rectangular patch antenna - Tan, Yong Meng, 1984-; You, Kok Yeow; Fakulti Kejuruteraan Elektrik (2009)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2009